2023
DOI: 10.1109/jbhi.2022.3212479
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Neighborhood Rough Set-Based Feature Selection Method and Its Application to Biomarker Identification of Schizophrenia

Abstract: Feature selection can disclose biomarkers of mental disorders that have unclear biological mechanisms.Although neighborhood rough set (NRS) has been applied to discover important sparse features, it has hardly ever been utilized in neuroimaging-based biomarker identification, probably due to the inadequate feature evaluation metric and incomplete information provided under a singlegranularity. Here, we propose a new NRS-based feature selection method and successfully identify brain functional connectivity biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Radiomics [15] [28] and various deep-learning techniques [29] [30] [31] have been widely applied in various clinical studies in recent years, such as detection of prostate cancer lesions [32], benignmalignant classi cation of lesions [33], and prediction of prognosis [34] [35] [36]. For instance, the study by Yi's team [12] con rmed that radiomics features can effectively identify malignant lesions that appear negative in PET/CT, and scholars such as Yao et al [37] have demonstrated that radiomics features can e ciently diagnose lymph node metastasis and extracapsular extension in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics [15] [28] and various deep-learning techniques [29] [30] [31] have been widely applied in various clinical studies in recent years, such as detection of prostate cancer lesions [32], benignmalignant classi cation of lesions [33], and prediction of prognosis [34] [35] [36]. For instance, the study by Yi's team [12] con rmed that radiomics features can effectively identify malignant lesions that appear negative in PET/CT, and scholars such as Yao et al [37] have demonstrated that radiomics features can e ciently diagnose lymph node metastasis and extracapsular extension in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have attempted to integrate machine learning and data analysis techniques to uncover the global alterations and disrupted patterns of brain functional connectivity in psychiatric disorders. A major aim has been to identify robust biomarkers facilitating comprehensive understanding of the neural mechanisms underlying these diseases [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%